1999
DOI: 10.2337/diacare.22.4.580
|View full text |Cite
|
Sign up to set email alerts
|

Biopsychobehavioral model of risk of severe hypoglycemia. Self-management behaviors.

Abstract: Subjects with a history of SH did not report managing their diabetes differently from those with no such history. Specifically, when low BG occurred, the preceding management behaviors, although predictive of low BG, were not different in SH and No-SH subjects. Overall, self-management behaviors did not distinguish SH from No-SH subjects. Thus, even though it might be beneficial for all patients to review their food and exercise management decisions to reduce their frequency of low BG, an educational intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…This is consistent with a recent study demonstrating that patients with a history of SH during the previous year showed less effective behavior regarding preventing low blood glucose levels, recognizing decreasing blood glucose levels and self-treatment of hypoglycemia (16). In addition, patients experiencing SH may need support to deal with a heightened fear of hypoglycemia.…”
Section: Hypoglycemia Awarenesssupporting
confidence: 80%
“…This is consistent with a recent study demonstrating that patients with a history of SH during the previous year showed less effective behavior regarding preventing low blood glucose levels, recognizing decreasing blood glucose levels and self-treatment of hypoglycemia (16). In addition, patients experiencing SH may need support to deal with a heightened fear of hypoglycemia.…”
Section: Hypoglycemia Awarenesssupporting
confidence: 80%
“…Two treatment modalities are the ingestion of carbohydrate and an adjustment in medication(s). A logistic regression analysis of 6,425 self-monitored blood glucose events in 93 adults with type 1 diabetes showed that more insulin, less food, or more exercise predicted 61% of all blood glucose values Ͻ70 mg/dl (Ͻ3.9 mmol/l), but did not predict severe hypoglycemia (580). Although rigid definitions of hypoglycemia are useful for epidemiological studies, more flexible definitions are needed in the management of diabetes.…”
Section: Technical Reviewmentioning
confidence: 99%
“…Altobelli et al (1) studied 70 patients aged from 10 to 18 years and found age to be a factor in monitoring, with adolescents less likely to be daily monitors of their diabetes. Clarke et al (24) studied 93 type 1 diabetics and found no predictors of regular monitoring. Gregg et al (36) also found no features common to monitoring in a study of 625 African American adults.…”
Section: What Characterizes Patients More Likely To Manage Disease Efmentioning
confidence: 99%